Greenness assessment of supply chains via intuitionistic fuzzy based approaches. (October 2021) - Topgul, Mete Han; Kilic, Huseyin Selcuk; Tuzkaya, Gulfem
Highlights: A systematic methodology is proposed for the greenness assessment of supply chains. In-bound, out-bound, in-plant, and reverse logistics activities of supply chains are considered in detail. A comprehensive list of Key Performance Indicators for greenness assessment is provided. IF-DEMATEL and IF-ANP are used within the greenness assessment methodology. An application is performed in an international fast moving consumer goods company. Abstract: The increase in the consumption level of products with various materials has resulted in many problems. A worrisome result of this situation is environmental problems. Thus, environmental considerations during the planning, designing, implementation, and controlling of business activities in the entire supply chain have taken more attention in recent years. Therefore, many studies have been performed considering the greenness of different activities within supply chains. Greenness assessment of supply chains is one of the most critical and essential subjects of the related literature. The companies can learn their weak sides and provide the required amendments to improve their supply chains' greenness as a result of the assessment. Hence, in this study, a greenness assessment methodology is proposed for four logistics stages including in-bound, in-plant, out-bound, and reverse logistics. By investigating the greenness of different logistics stages separately, their characteristics can be analyzed in a more systematic way. Also, a detailed KPI determination process is realized, and a comprehensive KPI set is proposed for all the logistics stages for the first time in the literature. Moreover, as another novelty, a methodology based on intuitionistic fuzzy-based techniques, an integrated IF-DEMATEL and IF-ANP approach, is utilized for the greenness assessment. The related steps of the developed methodology are explicitly provided within the study, an application is realized for a company, and results are analyzed in a detailed way.